The Evolution of EU Law on Refugees and Asylum - Tsourdi, Evangelia Lilian; Costello, Cathryn (Oxford University Press, 2021)
This chapter examines the evolution of EU law and policy on asylum and refugees, arguing that in spite of many institutional and legal changes, there is substantive stasis. The institutional and legal changes include a shift in the telos of EU asylum policy, repeated legislative amendments, and a shift from decentralized to increasingly integrated administration. Nonetheless, the chapter argues there has been substantive stasis, in that core features of EU asylum policy remain unchanged, notwithstanding their ‘crisis’ generating character. It argues that this state of affairs is due to the foundational tensions in this policy area, namely the tension between the aim of deflecting refugees elsewhere, and commitment to international protection; and the EU’s commitment to internal mobility, and the immobilization of asylum seekers and refugees. In light of these foundational tensions, two current trends are identified, namely an increasing turn to further EU-level administration, and a ‘flight from law’ in various key areas.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Access to asylum; Asylum harmonization; European asylum policy; European courts; Externalization; Integrated european administration; Practical cooperation; Refugee protection; Refugee resettlement; Responsibility-sharing